2020
DOI: 10.1080/09638180.2020.1852095
|View full text |Cite
|
Sign up to set email alerts
|

Tax Misperception and its Effects on Decision Making – Literature Review and Behavioral Taxpayer Response Model

Abstract: Previous accounting research shows that taxes affect decision making by individuals and firms. Most studies assume that agents have an accurate perception regarding their tax burden. However, there is a growing body of literature analyzing whether taxes are indeed perceived correctly. We review 128 studies on the measurement of tax misperception and its behavioral implications. The review reveals that many taxpayers have substantial tax misperceptions that lead to biased decision making. We develop a Behaviora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 148 publications
0
14
0
Order By: Relevance
“…While details are usually measured by counting the number of regulations, paragraphs or words (Clotfelter, 1983;Karlinsky, 1981;Weber, 2015;Weinstein, 5 See Slemrod (1989), McCaffery (1990), Cooper (1993), , Diller et al (2013) or Hoppe et al (2018). 6 An overview of research on perception and misperception of taxes including tax complexity and its implications for decision-making is provided by Blaufus et al (2020). 7 A literature review on the measurement of tax (bureaucracy) costs is provided by Eichfelder (2011).…”
Section: Review Of Existing Measurement Approachesmentioning
confidence: 99%
“…While details are usually measured by counting the number of regulations, paragraphs or words (Clotfelter, 1983;Karlinsky, 1981;Weber, 2015;Weinstein, 5 See Slemrod (1989), McCaffery (1990), Cooper (1993), , Diller et al (2013) or Hoppe et al (2018). 6 An overview of research on perception and misperception of taxes including tax complexity and its implications for decision-making is provided by Blaufus et al (2020). 7 A literature review on the measurement of tax (bureaucracy) costs is provided by Eichfelder (2011).…”
Section: Review Of Existing Measurement Approachesmentioning
confidence: 99%
“…Our contribution also adds to the literature devoted to the analysis of the consequences of information provision in a variety of economic applications, including job search (Altmann et al (2018), Belot et al (2018), Crépon et al (2018), Darling et al (2016)), labor supply and taxes (Chetty and Saez (2013), Blaufus et al (2020)), the take-up of social benefits (Currie (2006), Bhargava and Manoli (2015), Finkelstein and Notowidigdo (2019)), unemployment benefits (Blank and Card (1991), Fontaine and Ketteman (2019)), housing allowances (Engström et al (2015)), retirement savings plans (Dolls et al (2019)) and training programs (Crépon et al (2018). From this perspective, our paper is the first to provide information about part-time unemployment benefits.…”
Section: Introductionmentioning
confidence: 98%
“…Researches have confirmed that taxes significantly influence decision making, i.e., decisions for investment and financing (Blaufus & Chirvi, 2020). Behavioral response to an investment provides insights into perception of the individuals.…”
Section: Introductionmentioning
confidence: 99%